2018
DOI: 10.1002/pmh.1417
|View full text |Cite
|
Sign up to set email alerts
|

Links between depression and openness and its facets

Abstract: Most studies on depression and personality have focused on the role of Neuroticism and Extraversion. Openness is a much less studied trait in this literature, as past studies investigating Openness and depression often have found non-significant correlations between them. However, past studies mostly have investigated Openness and depression at the domain level and used non-clinical samples. In the present study, the relationship between depression and Openness at the domain and facet levels was examined in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 45 publications
1
14
1
2
Order By: Relevance
“…Next, extraversion, openness, and conscientiousness had significantly negative predictive effects on the intercept of the depressive mood of first-year high school students. These findings supported prior reports that depressive mood is predicted negatively by extraversion, openness, and conscientiousness (Hakulinen et al, 2015;Khoo & Simms, 2018;Kim et al, 2016). The reason may be that extraversion, openness, and conscientiousness have positive effects on individuals, such as improving interpersonal relationships (Harris et al, 2017;Jensen-Campbell & Malcolm, 2007), effectively coping with stress (Kim et al, 2016), and obtaining academic achievement (Wagerman & Funder, 2007).…”
Section: Influence Of Personality On Depressive Mood Over Timesupporting
confidence: 88%
See 2 more Smart Citations
“…Next, extraversion, openness, and conscientiousness had significantly negative predictive effects on the intercept of the depressive mood of first-year high school students. These findings supported prior reports that depressive mood is predicted negatively by extraversion, openness, and conscientiousness (Hakulinen et al, 2015;Khoo & Simms, 2018;Kim et al, 2016). The reason may be that extraversion, openness, and conscientiousness have positive effects on individuals, such as improving interpersonal relationships (Harris et al, 2017;Jensen-Campbell & Malcolm, 2007), effectively coping with stress (Kim et al, 2016), and obtaining academic achievement (Wagerman & Funder, 2007).…”
Section: Influence Of Personality On Depressive Mood Over Timesupporting
confidence: 88%
“…Overall, cross-sectional research shows that neuroticism is positively related to individuals' depressive mood (Hakulinen et al, 2015;Kendler et al, 2004;Smith et al, 2018), whereas extraversion, openness, conscientiousness, and agreeableness are negatively related to depressive mood (Hakulinen et al, 2015;Kim et al, 2016;Khoo & Simms, 2018;Shi et al, 2015). In addition, both neuroticism and extraversion affect the development of depressive mood (Eeden et al, 2019;Spinhoven et al, 2014).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast to the literature, we found that people with higher levels of openness experienced higher levels of depression, anxiety, and loneliness. However, this result could be explained by different facets of this personality trait, especially fantasy, which may lead to experiencing higher discrepancies between idealized and actual self- or world-states and come with a higher risk for depression ( 65 ). We found that people scoring high in conscientiousness are experiencing lower stress levels inconsistent with pre-pandemic studies ( 66 , 67 ), suggesting that higher conscientiousness may be beneficial in adjusting to pandemic control measures and accepting the new situation.…”
Section: Discussionmentioning
confidence: 99%
“…De acuerdo con Khoo y Simms (2018), las personas que obtienen un puntaje alto en la faceta 'sentimientos' son más propensas a experimentar una gama más amplia de emociones, tanto positivas como negativas, lo que puede incluir emociones relacionadas con la depresión. Asimismo, aquellos individuos con puntajes altos en la faceta 'fantasía' podrían experimentar una mayor discrepancia entre el estado idealizado de sí mismos y del mundo y el estado real (Khoo & Simms, 2018). Por otra parte, se ha observado que la apertura se encuentra vinculada a la ideología política (Lee, Ashton, Ogunfowora, Bourdage, & Shin, 2010;Hiel, Kossowska, & Mervielde, 2000;Hiel & Mervielde, 2004).…”
Section: Apertura a La Experienciaunclassified